Perfectionism and the relationship with psychopathologies: Integrative study (Research, Society and Development, 2021)
Perfectionism is a latent psychological trait that has been understood in several different ways. Scientific and methodological advances in the area suggest that this phenomenon has both positive and negative components. Motivated by the question raised: what are the main psychopathologies, currently, related to perfectionism? Some discussions are promoted from this point of view. To this end, this article condenses, organizes and presents an integrative review consulted on national and international bases and aimed to investigate which are the main psychopathologies related to perfectionism. Thus, searches for articles were performed in the Medline, Pubmed and Springer databases with the descriptors perfectionism, psychopathology, perfectionism and psychopathology, both recruited from DeCS and MeSH. Of the 226 articles found initially, 213 were discarded as the inclusion and exclusion criteria were applied. Thus, 13 articles made up the final sample. The results indicated that perfectionism has been related to depression, anxiety, eating disorders (bulimia and anorexia) as well as obsessive compulsive disorder. Limitations and suggestions for future studies are discussed at the end.